International Architecture News - Grigorieva, Anna (project baikal, 2025)
The news section announces the 5th edition of the Friendly and Inclusive Spaces Awards and the 20th edition of the Global Award for Sustainable Architecture. It also presents the results of the 7th Baku International Architecture Award.